MASS COMMUNICATION AND FEMALE SHAPING POWER - KULCSÁR, Erika; CSOMA, Tünde; FÜLÖP, Noémi; SZONDA, Noémi; TIMÁR, Kinga-Izabella; VITÁLYOS, Dorottya (Studia Universitatis Babeș-Bolyai Negotia, 2018)
Communication was born at the same time with humanity, and with the progression of historical ages the range of communication opportunities has become more widespread. Communication has the power, whether transmitted by words, images or even behavior, to shape the individual and thus the society. The greatest power of communication is its shaping potential. Individuals, organizations, companies, and governments are aware that what is being conveyed has an impact on the social values, but they also play a role in promoting societal problems, as empathy is the cornerstone of a healthy society. This article analyzes the following: (1) by what means and how did the communication of the expectations on women change during history (physical values/values regarding the appearance); (2) identifying the social problems of advertising campaigns; (3) the main guiding principle of Apple, Huawei and Samsung's advertising: the focus of their communication; (4) the values determined by Julia Roberts and the brands she represents; (5) the social problems promoted by world brands. The focus of the analyzes is on women, because women play a significant role in the implementation and solution of values and social problems, they also have an important role to play if they do not fight in the front line, but they are behind the scenes. JEL classification: L82